A Combined Energy–Exergy Approach for Improving Refrigeration Systems in Deep-Level Gold Mines: Method Development and Case Study Validation - Du Randt, Johannes Claudius (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.